2013
DOI: 10.1002/jbm.a.34894
|View full text |Cite
|
Sign up to set email alerts
|

Formation of thermo‐sensitive polyelectrolyte complex micelles from two biocompatible graft copolymers for drug delivery

Abstract: Thermo-sensitive polyelectrolyte complex (PEC) micelles assembled from two biocompatible graft copolymers chitosan-g-poly(N-isopropylacrylamide) (CS-g-PNIPAM) and carboxymethyl cellulose-g-poly(N-isopropylacrylamide) (CMC-g-PNIPAM) were prepared for delivery of 5-fluorouracil (5-FU). The PEC micelles showed a narrow size distribution with core-shell structure, in which the core formed from positively charged CS and negatively charged CMC by electrostatic interactions and the shell formed from thermo-sensitive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Based on these mechanisms, the drug release of 5-FU at 37 °C was higher than that released at 25 °C. This behavior demonstrated that the release rate of 5-FU was controlled by changing external conditions [ 176 , 177 ].…”
Section: Micelles In Tumor Targeted Drug Releasementioning
confidence: 99%
“…Based on these mechanisms, the drug release of 5-FU at 37 °C was higher than that released at 25 °C. This behavior demonstrated that the release rate of 5-FU was controlled by changing external conditions [ 176 , 177 ].…”
Section: Micelles In Tumor Targeted Drug Releasementioning
confidence: 99%
“…These injectable DDSs can be designed to exploit the physical abnormalities of the stiff ECM that exist in tumors (altered structural and vasculature tumor microenvironment, uneven blood flow, high interstitial pressure, poor elasticity, heterogeneous vessel permeability, and metabolic autonomy). In addition, tumor tissue exhibits elevated temperatures that reach 40–42 °C, as compared with most healthy tissues that exhibit temperatures near 32 °C. , High rates of glycolysis and rapid proliferation are thought to contribute to these elevated tumor temperatures, and temperature induced drug activation is actively being explored.…”
Section: In Situ Forming Hydrogels Enable Ecm Targeted Therapymentioning
confidence: 99%
“…Aldehydes, ketones, and carboxylic acids are essential industry products and intermediates 1 . Among them, aldehydes, 2–5 carboxylic acids, 6–8 amides, 9,10 and other derivatives are commonly found in literature as starting materials or building blocks in several synthetic methodologies. These derivatives are commonly prepared by oxidation of the corresponding alcohols as reported in literature 11 ; in this regard, organic solvents and nongreen oxidants (CrO 3 , NaClO, KMnO 4 , etc.)…”
Section: Introductionmentioning
confidence: 99%